Programming for specific purposes in linguistics: A new challenge for the humanitarian curricula - Alexey I. Gorozhanov; Innara A. Guseynova (Peoples' Friendship University of Russia (RUDN University), 2020)
The article describes the ways of teaching the linguistic students programming for specific purposes and deals with the global problem of training future teachers of a foreign language and culture in the context of digitalisation. The issues related to the linguistic component in teaching programming are also revealed in the framework of the paper. An innovative tutorial in programming on Python is described as an example, which is built on the classical principles of comparison, contrast and 'from simple to complex', and considers the following topics: basic operations on Python (Part 1), basic knowledge about the PyQt5 graphics library (Part 2) and introduction to developing web applications on the web2py framework (Part 3). The tutorial is provided with examples of programming code and screenshots of the application interfaces. Part 1 of the tutorial is mandatory for learning, as it is intended for developing basic skills of programming (active learning) that can help the students to understand the structure of the algorithms analysed in the 2nd and the 3rd parts (passive learning). The first two parts of the tutorial were tested by the students of the German Faculty at Moscow State Linguistic University (about 150 people in total in the period from 2018 to 2020). Most of the students successfully coped with the Part 1 tasks, which were actually the goal of the work. Though a deep understanding of the materials of Part 2 was achieved by 5% of the students, this could be considered a success, especially since some of them used programming methods for their research. The conclusion draws upon the results of the testing of the tutorial. The proposed approach to teaching the linguistic students skills in programming for specific purposes seems to be promising and effective.